UV Resistance and Photoreactivation of Extremophiles from High-Altitude Andean Lakes - Albarracín, Virginia Helena (2013)
He HAAL are natural laboratories for exploring and monitoring in situ interactions between the geophysical environment and the dynamics of biodiversity. Solar irradiation (including high UV-B doses) is without doubt the factor that puts the greatest pressure on the ecology of the microbial communities thriving in these shallow lakes. Thus, it is not surprising that ~100 strains with intrinsic UV-B-resistance have been isolated from HAAL. These organisms have developed strategies to cope with strong UV-B irradiation to avoid severe UV-B-damage to proteins, lipids and DNA. Hence, microbiota at the HAAL may harbor special mechanisms to sense and respond to such a ubiquitous resource, i.e., light. In accordance with this, we have encountered a rich diversity of photoreceptors within the cryptochrome-photolyase family in the genomes of three UV-B-resistant extremophiles. Of particular importance among these photoreceptors was the finding of a photolyase-coding sequence in the genome of Acinetobacter sp. Ver3 strain that displayed efficient photoreactivation ability after strong UV-B-induced DNA damage. Based on sequence alignments and secondary structure predictions for this novel photolyase, and entries in the PDB, we found the highest three-dimensional similarity to the photolyase from E. coli (PDB 1DNPA). The structure revealed a proximal alpha-beta domain, and a distal helical domain that binds to FAD in full accordance to the structure of the E. coli photolyase. The N-terminal anti-parallel bundle of beta sheets enclosed by alpha helices is a typical folding motif of photolyases. The chain of three-tryptophan residues instrumental for electron transfer reaction is also conserved in Ver3 photolyase, and in close proximity to the isoalloxazine ring of FAD. All the former findings support the putative CPD-photolyase property of this protein, and agree with the efficient ability of Ver3 for repairing CPD lesions. Nevertheless, a more detailed functional characterization of this "extremoenzyme" is being conducted at the moment to clarify its repair function. The scenario pictured herein makes the HAAL microorganisms excellent test cases for exploring novel enzymatic functions driven by light, and for the bioprospection of novel molecules with potential biotechnological applications on energy conversion, biomedicine or industry. This brief overview is intended to "shine" scientific light on a high window from a quite unexplored, exotic environment, which otherwise constitutes an exceptional outdoor photobiology lab.